Left-behind regions in the European Union: Conceptualisation – Operationalisation – Classification - Josef Bernard; Martin Refisch; Tomáš KosteleckAý; Anna Grzelak; Michał Konopski; Andreas Klärner (Johann Heinrich von Thünen-Institut, 2025)
The concept of left-behind places or regions has skyrocketed in recent years and various empirical studies are using the concept to describe (not only) economically lagging regions. Yet, there is still no settled definition and method of measurement of left-behindness in the social sciences. In the methodological part this working paper presents a plausible conceptualisation and operationalisation of left-behind regions in European Union countries. The operationalization of "left-behindness" is guided by several principles: it is relative to national standards, multidimensional, and both structural and dynamic. Labour market regions are identified as the appropriate spatial unit for analysis. The study uses NUTS3 regions, aggregated for metropolitan areas and adjacent regions, excluding extraterritorial and small countries. A total of 918 regions across 25 countries are analysed using indicators related to economic viability, social structure, and population development from 1993 to 2021. Our empirical analysis highlights how the nature of "left-behindness" varies across Europe, with a particular focus on Central and Eastern Europe. In these regions, left-behindness is closely tied to regional disadvantages, characterized by low economic prosperity, reduced social status, and higher poverty rates. These areas often experience stagnation or shrinkage, with non-metropolitan regions being particularly affected, possibly due to poorer infrastructure. In other parts of Europe, the different dimensions of left-behindness are less coherently associated and do not form clear spatial patterns. In particular, poverty is spatially decoupled from low economic prosperity in many countries. Overall, we identified macro-regional differences of left-behindness manifestation across Europe, shaped by historical, economic, and social factors unique to each region. – – Das Konzept der "abgehängten" Orte oder Regionen hat in den vergangenen Jahren stark an Bedeutung gewonnen, und verschiedene empirische Studien verwenden das Konzept, um (nicht nur) wirtschaftlich rückständige Regionen zu beschreiben. Dennoch gibt es in den Sozialwissenschaften bislang keine einheitliche Definition und Methode zur Messung von "Abgehängtsein". Im methodischen Teil dieses Thünen Working Papers wird eine neue Konzeptualisierung und Operationalisierung von "abgehängten" Regionen vorgestellt. Die Operationalisierung von "Abgehängtsein" orientiert sich an mehreren Prinzipien: Sie ist relativ zu nationalen Standards, multidimensional und sowohl strukturell als auch dynamisch. Arbeitsmarktregionen werden als geeignete räumliche Einheit für die Analyse festgelegt. Die Studie verwendet dafür NUTS3-Regionen und aggregiert dabei Großstadtregionen und angrenzende Regionen. Insgesamt 918 Regionen in 25 Ländern werden anhand von Indikatoren für die wirtschaftliche Lebensfähigkeit, die Sozialstruktur und die Bevölkerungsentwicklung von 1993 bis 2021 analysiert. Unsere empirische Analyse zeigt, wie "Abgehängtsein" in Europa variiert, wobei der Schwerpunkt auf Mittel- und Osteuropa liegt. In diesen Regionen ist "Abgehängtsein" eng mit regionalen Benachteiligungen verbunden, die durch geringen wirtschaftlichen Wohlstand und höhere Armutsraten gekennzeichnet sind. Diese Gebiete sind häufig von Stagnation oder Schrumpfung betroffen, wobei die nicht-metropolitanen Regionen besonders betroffen sind, was möglicherweise auf eine schlechtere Infrastruktur zurückzuführen ist. In anderen Teilen Europas sind die verschiedenen Dimensionen des "Abgehängtseins" weniger kohärent miteinander verbunden und bilden keine klaren räumlichen Muster. Insbesondere Armut ist in vielen Ländern räumlich von einem geringen wirtschaftlichen Wohlstand entkoppelt. Insgesamt haben wir für Europa regionale Unterschiede in der Ausprägung des "Abgehängtseins" festgestellt, die durch historische, wirtschaftliche und soziale Faktoren geprägt sind und für jede Region einzigartig sind.
urn:nbn:de:gbv:253-2501211020158.969627513268
Keywords: F63; O18; R11; R12; 630; left-behind regions; European Union; abgehängte Regionen; Europäische Union